MODEL PEMBERDAYAAN WAKAF PRODUKTIF DI INDONESIA (UIN Sunan Kudus, 2014)
Through empowerment productive endowments, charitableinstitutions have run most tasks of government institutions, or specialministries such as the ministry of education, ministry of health, social ministryand other ministries related to the needs of the community. This is because theempowerment endowment has been used to build the dormitory, library, hireteachers, pay teachers, provide scholarships to students, provide health care,clean water supply, help the hungry, and help the disaster in the community.In addition, it is also motivating the research and translation programs aresupported by the results of waqf. Many books written or translated by scholarsand Muslim scientists were funded from the endowment. Research that isdeveloped either by using empirical and scientific methods to be developedand supported by the endowment funding. This means making productiveendowments as a medium for creating economic justice, reducing indigenceand poverty, developing social security systems, and provide health carefacilities and public service facilities are good.